The Impact Of Educational Units Proposed By Small Games In The Development Of The Speed Of Transition And The Speed Of Reaction To Students. - Kadri, Abdelhafid; Yahiaoui, said (sports creativity, 2025)
This study was used to investigate the effect of the proposed units on the small games for the development of speed character (the speed and reaction speed) of a sample of first year students (11-12 years). The researcher used the experimental method using the experimental design of two groups (control and experimental) The sample of the study consisted of (70 students and students) of the students of first year (11-12 years), randomly selected to be divided into two groups, 35 students representing a control group applying the traditional program prepared by the professor of physical and sports education for the medium of Setif-Brikha road for the academic year 2015/2016 and experimental group The proposed program is applied in small games. In order to achieve the objectives of the study, two tests were chosen, one that measures the transition speed and the other the reaction speed. It is characterized by a high level of honesty, stability and objectivity. A small game program, which lasted 12 weeks, was designed for 12 units. There were statistically significant differences for the experimental group.